Regional Effects of Maternal Mortality Determinants in Africa and the Middle East: How About Political Risks of Conflicts? - Mamkhezri, Jamal; Razzaghi, Somayeh; Khezri, Mohsen; Heshmati, Almas (Frontiers in Public Health, 2022)
Background As per the United Nations Women data, the maternal mortality rate in war-affected countries is critical and more than 800 million people live in war-affected countries (ICRC). External and internal conflicts such as foreign pressure, war and cross-border, civil disorder, terrorism, and civil war, are characteristics of Middle Eastern and African countries. Therefore considering the rapid increment of political risks and internal and external conflicts in Africa and the Middle East during the last decade, and considering warfare as a key contributor to maternal mortality; This paper seeks to evaluate the factors that have caused significant rates of maternal mortality in Middle Eastern and African countries by emphasizing the contributions of a number of political risk aspects as Civil Disorder Index, Terrorism Index, Civil War Index, Foreign Pressures Index, Cross-Border Conflict Index, War Index along with other socio-economic factors. Method Data were collected from forty-six countries during 2011-2016 to explore the regional contributions of political risk aspects to the maternal mortality rate through spatial approaches. Results It was found that GDP per capita, energy intensity, and urbanization strongly impacted maternal mortality. Also, it was observed that natural resource rents and economic growth significantly influenced the reduction of mortality by expanding healthcare services. The urban expansion was found to have elevated maternal mortality. A majority of external and internal conflicts reduced the orientation of production toward healthcare services and thus raised maternal mortality. On the other hand, war and cross-border were found to pose opposite impacts. Conclusion The findings revealed that political risks arising from terrorism, foreign pressure, and war in the adjacent countries would elevate the rate of mortality in the original country. This implies the spillover impacts of regional conflicts on maternal mortality elevation at the regional scale.